Prevalence of Gastro-Intestinal Parasitic Infections and Efficacy of Antiparasitics Against These Infections in Dogs in Mymensingh Sadar (Research in Agriculture Livestock and Fisheries, 2020)
Gastro-intestinal parasitic infections in dogs represent a major concern in developing countries including Bangladesh. Dogs are important definitive or reservoir hosts for several zoonotic parasites. This study was conducted to determine the prevalence of gastro-intestinal parasites in dogs from different areas of MymensinghSadar. The fecal samples were examined by simple sedimentation and stoll’s ova counting method for detection of eggs/cysts/oocysts of parasites. The overall prevalence of gastrointestinal parasites was 60.00% (51/85) and the mixed parasitic infection was 16.47% (14/85). A total of six species of gastro-intestinal parasites (ova/oocyst) were identified, of them four species were nematode namely,Toxocaracanis (24.7%), Acylostomacaninum (7.05%), Acylostomabraziliense (2.35%), Uncinariastenocephala (2.35%), one species was cestode, Taeniapisiformis (3.52%) and one species was protozoa, Isosporacanis (3.52%). The prevalence of infection was significantly (P